Effects of dietary vitamin E on growth, immune response, antioxidant capacity, intestinal histomorphology, digestibility and disease resistance of juvenile Pacific white shrimp (Penaeus vannamei) - Daehyun Ko; Nalin Medagoda; Jaebeom Shin; Mirasha Hasanthi; Jinho Bae; Byung Hwa Min; Kyeong-Jun Lee (PLoS ONE, 2025)
Vitamin E (tocopherols, VE) is a lipid-soluble antioxidant involved in neutralizing reactive oxygen species and maintaining immune function in animals. This study aimed to determine the optimum dietary VE requirement of juvenile Pacific white shrimp (Penaeus vannamei) for growth, feed utilization, immune responses, antioxidative capacity, diet digestibility, intestinal histomorphology and disease resistance against Vibrio parahaemolyticus. Eight experimental diets were formulated to contain graded levels of VE (0, 20, 40, 60, 80, 100, 120 and 240 mg/kg; designated as VE0, VE20, VE40, VE60, VE80, VE100, VE120 and VE240). Four replicate groups, each containing 30 shrimp (0.20 ± 0.04 g), were fed one of the diets six times daily for 56 days. Shrimp fed VE80 diet exhibited significantly increased growth performance compared to shrimp fed VE0, VE20 and VE240 diets. Non-specific immune responses were significantly enhanced in shrimp fed VE60-VE80 diets. Hepatopancreatic lipid peroxidation in VE80 group was significantly lower compared to the VE0 group. The expression of Crustin, C-MnSOD and GPx genes in the hepatopancreas was significantly upregulated in VE80 group. Graded dietary VE levels significantly linearly increased hemolymph and hepatopancreas VE concentrations. Intestinal villi height and width were significantly improved with dietary VE supplementation. The digestibility of protein, lipid and dry matter was significantly higher in shrimp fed VE80 diet compared to those fed VE0 diet. The resistance against V. parahaemolyticus was significantly higher in shrimp fed VE80, VE100 and VE120 diets compared to those fed VE0 and VE20 diets. The optimal dietary VE level for Pacific white shrimp was estimated to be 72.17 mg/kg for weight gain and 72.21 mg/kg specific growth rate, based on broken-line analysis. In conclusion, optimal dietary VE supplementation enhances shrimp growth, immunity, antioxidative defense and disease resistance against V. parahaemolyticus, thereby reducing the risk of early mortality syndrome caused by acute hepatopancreatic necrosis disease.